2023
DOI: 10.1177/1357633x231166026
|View full text |Cite
|
Sign up to set email alerts
|

Association between broadband capacity and telehealth utilization among Medicare Fee-for-service beneficiaries during the COVID-19 pandemic

Abstract: Background Telehealth is a rapidly growing modality for expanding healthcare access, especially in the post-COVID-19 era. However, telehealth requires high-quality broadband, thus making broadband a social determinant of health. The objective of this study was to evaluate the association between broadband access and telehealth utilization across the United States during the COVID-19 pandemic. Methods Using a cross-sectional, ecological study design, we merged county-level data on broadband capacity (Microsoft'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Access to HSI emerged as a key factor related to telehealth use. These findings align with prior literature suggesting that HSI expansion would increase primary care receipt . However, differences in telehealth use by sex, geography, age, and income persisted among those with HSI, suggesting that HSI expansion would not close utilization gaps for these groups.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Access to HSI emerged as a key factor related to telehealth use. These findings align with prior literature suggesting that HSI expansion would increase primary care receipt . However, differences in telehealth use by sex, geography, age, and income persisted among those with HSI, suggesting that HSI expansion would not close utilization gaps for these groups.…”
Section: Discussionsupporting
confidence: 86%
“…These findings align with prior literature suggesting that HSI expansion would increase primary care receipt. 33 , 49 , 50 However, differences in telehealth use by sex, geography, age, and income persisted among those with HSI, suggesting that HSI expansion would not close utilization gaps for these groups. Adding complexity, exploratory analyses identified 20% of post-PHE visits as phone-only, inspiring mechanistic questions about how HSI promotes telehealth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, despite telehealth being an effective tool to support health care access in rural communities, rural patients were less likely to engage in telehealth during the COVID-19 pandemic compared with urban patients. 9 , 37 There also have been reported disparities in use of telehealth among different patient populations due to various demographic characteristics and social determinants of health. 8 , 9 , 11 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…However, the recent COVID-19 pandemic has exposed many disparities surrounding key digital determinants of health. 6,7 Although recent research has shown greater telehealth use in areas of better broadband access, 8 more than 25% of the US population still lacks proper access to broadband internet. 9 Furthermore, older adults with chronic disease tend to use telemedicine less than adults younger than 56 years, 10 as some do not feel confident navigating telehealth platforms or accommodating to smaller screens and text.…”
mentioning
confidence: 99%